Shear Speed-Regulated Properties of Long-Acting Docetaxel Control Release Poly (Lactic-Co-Glycolic Acid) Microspheres - Zheng, Yuhao; Sheng, Fan; Wang, Zihang; Yang, Guang; Li, Chenguang; Wang, He; Song, Zhiming (Frontiers in Pharmacology, 2020)
Advanced drug carriers for the controlled release of chemotherapeutics in the treatment of malignant tumors have drawn significant notice in recent years. In the current study, microspheres (MPs) loaded with docetaxel (DTX) were prepared using polylactic-co-glycolic acid copolymer (PLGA). The double emulsion solvent evaporation method is simple to perform, and results in high encapsulation efficiency. Electron micrographs of the MPs showed that controlling the shear rate can effectively control the size of the MPs. At present, most DTX sustained-release carriers cannot maintain stable and long-term local drug release. The 1.68 μm DTX-loaded microspheres (MP/DTX) with elastase was completely degraded in 14 d. This controlled degradation period is similar to a course of treatment for most cancers. The drug release profile of all kinds of MP/DTX demonstrated an initial rapid release, then slower and stable release to the end. The current study demonstrates that it is possible to create drug-loaded MPs with specific degradation times and drug release curves, which may be useful in achieving optimal treatment times and drug release rates for different diseases, and different drug delivery routes. The initial burst release reaches the effective concentration of the drug at the beginning of release, and then the drug concentration is maintained by stable release to reduce the number of injections and improve patient compliance.